2009
DOI: 10.1002/j.2055-2335.2009.tb00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Acceptance of a Pharmacist‐Initiated E‐Script Transcription Service for Discharge Prescriptions

Abstract: Aim To describe the implementation of pharmacist‐initiated e‐script transcription service (PETS) in a teaching hospital; to validate the service through process indicators; and to explore the views of stakeholders. Method Following an initial trial, PETS was implemented in 7 medical and surgical units at Frankston Hospital. Data were collected on activities and discharge prescription errors. Stakeholders' satisfaction was measured using a Likert scale based survey and group interviews. Transcripts of group int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…These outcomes have confirmed previous study results of PETS pharmacist prescription having reduced medication errors. [9][10][11] Control group results are comparable to error rates seen at preadmission, which can suggest that errors in the perioperative setting can translate to inpatient errors and subsequently discharge prescription errors, that ultimately leads to errors on the GP discharge summary. Complete and accurate documentation of a patient's medications is vital in communication between health-care professionals, especially around the time of surgery to clearly identify what has been ceased due to the surgery or suspended for a period of time due to surgical risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These outcomes have confirmed previous study results of PETS pharmacist prescription having reduced medication errors. [9][10][11] Control group results are comparable to error rates seen at preadmission, which can suggest that errors in the perioperative setting can translate to inpatient errors and subsequently discharge prescription errors, that ultimately leads to errors on the GP discharge summary. Complete and accurate documentation of a patient's medications is vital in communication between health-care professionals, especially around the time of surgery to clearly identify what has been ceased due to the surgery or suspended for a period of time due to surgical risks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted to evaluate the service showed a reduction in prescribing errors and a decrease in time taken to discharge patients when discharge prescriptions were prepared by PETS pharmacists instead of doctors. [9][10][11] To our knowledge, there is currently no study that closes the loop in surgical patient's medication management by a pharmacist, from perioperative period to discharge. Therefore, we combined the perioperative pharmacist role with PETS to create the PeRiopErative and Prescribing (PREP) pharmacist.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, this 400‐bed Australian metropolitan hospital implemented a successful Pharmacist‐initiated e‐script Transcription Service whereby an experienced pharmacist undertook discharge medication reconciliation and generation of an electronic discharge prescription, which was printed and signed off by the referring medical officer. This project resulted in statistically significant improvements in the quality, accuracy ( P = 0·0005) and timeliness of discharge prescriptions ( P = 0·02) …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Pharmacists are ideally placed to improve the accuracy of medication documentation, with previous studies showing improvement in accuracy both at discharge and at various timepoints in a patient's hospital journey. [12][13][14][15][16][17][18] Pharmacist input reduces medication errors and improves patient outcomes. 19,20 A pharmacist-led partnered prescribing (PPP) workflow was developed in response to an internal audit of our hospital network which found two-thirds of discharge summaries contained a medication documentation error.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists are ideally placed to improve the accuracy of medication documentation, with previous studies showing improvement in accuracy both at discharge and at various timepoints in a patient's hospital journey 12–18 . Pharmacist input reduces medication errors and improves patient outcomes 19,20 …”
Section: Introductionmentioning
confidence: 99%